Numerical Simulation and Analysis of Water and Suspended Sediment Transport in Hangzhou Bay, China - Ju Huang; Rui Yuan; Jianrong Zhu (Journal of Marine Science and Engineering, 2022)
Hangzhou Bay is a large, high-turbidity shallow bay located on the southern side of the Changjiang Estuary, China. The process and dynamic mechanisms of water and sediment transport in the bay are not yet clear. An improved three-dimensional sediment numerical model that combined various dynamic factors was established to simulate and analyze these mechanisms. The residual current cannot properly represent the net water and sediment transport, and the residual unit width water flux (RUWF) and residual unit width sediment flux (RUSF) were used to explain the water and sediment transport. The results of numerical simulations indicate that in summer, the surface RUWF from the Changjiang Estuary near Nanhui Cape flows westward along the coast, in which the major part flows southward to the Zhenhai area, and the small part flows further westward along the north coast and then turns to the south coast and eastward, forming the water transport pattern of north-landward and south-seaward, which is stronger in the spring tide than in the neap tide. The bottom RUWF near Zhenhai flows northward to Nanhui Cape in the neap tide, which is larger in the neap tide than in the spring tide. In the middle and western parts of the bay, the RUWF has the same pattern as the surface water transport and is stronger in the spring tide than in the neap tide. The pattern of RUSF is roughly similar to the water flux transport. During the spring tide, the water and sediment transport fluxes near Nanhui Cape are from the Changjiang Estuary into Hangzhou Bay, but from Hangzhou Bay into the Changjiang Estuary during the neap tide. In the winter, the distributions of RUWF, RUSF, and suspended sediment concentration (SSC) are similar to those in the summer. In addition, the distance of surface water transport westward along the north coast is shorter than that in the summer, the magnitude of the bottom RUWF is smaller than that in the summer due to the weaker salinity gradient, and the bottom RUSF near Nanhui Cape is weaker than that in the summer during the neap tide. The net transect water flux (NTWF) and the net transect sediment flux (NTSF) near Nanhui Cape are from the Changjiang Estuary into Hangzhou Bay during the spring tide; during the neap tide, the NTWF is still from the Changjiang Estuary into Hangzhou Bay, but the NTSF is from Hangzhou Bay into the Changjiang Estuary because the SSC is much higher in the bottom layer than in the surface layer. The dynamic reason for the temporal and spatial variation in RUWF and RUSF is that the barotropic pressure gradient force is larger than the baroclinic pressure gradient force during the spring tide and is the opposite during the neap tide.